The impact of remittances on poverty in Africa: A cross-country empirical analysis - Mahlalela, Noxolo (School of Economics, 2017)
Very limited empirical studies exist on the impact of remittances on poverty in Africa. To fill this gap in the literature, this study analyses the impact of remittances on poverty in a panel of 32 African countries. The study expands upon earlier work by including two additional foreign currency inflows, exports and Official Development Assistance (ODA). Accounting for possible heteroscedasticity and endogeneity, the results consistently show that remittances significantly reduce poverty. Exports and ODA are found to have a statistically insignificant effect on poverty. The absence of a significant relationship between exports, ODA and poverty suggest that the growth gains from exports and ODA fail to trickle down to the poor. These results highlight the significance of remittances as a source of finance for development.